Survival with Trastuzumab Emtansine in Residual HER2-Positive Breast Cancer - Geyer, Charles E.; Untch, Michael; Huang, Chiun Sheng; Mano, Max S.; Mamounas, Eleftherios P.; Wolmark, Norman; Rastogi, Priya; Schneeweiss, Andreas; Redondo, Andres; Fischer, Hans H.; D'Hondt, Véronique; Conlin, Alison K.; et al. (New England Journal of Medicine, 2025)
BACKGROUND: Patients with human epidermal growth factor receptor 2 (HER2)-positive early breast cancer with residual invasive disease after neoadjuvant systemic therapy have a high risk of recurrence and death. The primary analysis of KATHERINE, a phase 3, open-label trial, showed that the risk of invasive breast cancer or death was 50% lower with adjuvant trastuzumab emtansine (T-DM1) than with trastuzumab alone. METHODS: We randomly assigned patients with HER2-positive early breast cancer with residual invasive disease in the breast or axilla after neoadjuvant systemic treatment with taxane-based chemotherapy and trastuzumab to receive T-DM1 or trastuzumab for 14 cycles. Here, we report the prespecified final analysis of invasive disease-free survival and the second interim analysis of overall survival. RESULTS: With a median follow-up of 8.4 years, T-DM1 sustained the improvement in invasive disease-free survival over trastuzumab (unstratified hazard ratio for invasive disease or death, 0.54; 95% confidence interval [CI], 0.44 to 0.66). Seven-year invasive disease-free survival was 80.8% with T-DM1 and 67.1% with trastuzumab (difference, 13.7 percentage points). T-DM1 also led to a significantly lower risk of death than trastuzumab (unstratified hazard ratio, 0.66; 95% CI, 0.51 to 0.87; P = 0.003). Seven-year overall survival was 89.1% with T-DM1 and 84.4% with trastuzumab (difference, 4.7 percentage points). Adverse events of grade 3 or higher were noted in 26.1% of the patients in the T-DM1 group and 15.7% of those in the trastuzumab group. CONCLUSIONS: As compared with trastuzumab, T-DM1 improved overall survival with sustained improvement in invasive disease-free survival among patients with HER2-positive early breast cancer with residual invasive disease after neoadjuvant therapy. (Funded by F. Hoffmann-La Roche/Genentech; KATHERINE ClinicalTrials.gov number, NCT01772472.).
CRIS-Team Scopus Importer:2025-01-31